Taxonomy of the Narcissus Flycatcher Ficedula narcissina complex: an integrative approach using morphological, bioacoustic and multilocus DNA data. (25th February 2015) - Dong, Lu; Wei, Min; Alström, Per; Huang, Xi; Olsson, Urban; Shigeta, Yoshimitsu; Zhang, Yanyun; Zheng, Guangmei
Abstract : The taxonomy of the Narcissus Flycatcher Ficedula narcissina– Yellow‐rumped Flycatcher Ficedula zanthopygia complex from East Asia has long been debated. Most authors recognize two species: F. narcissina, with the subspecies narcissina (most of Japan and Sakhalin Island), owstoni (south Japanese islands) and elisae (northeast China) and F. zanthopygia (monotypic), although species status has been proposed for elisae and sometimes for owstoni . Here, we revise the taxonomy of this complex based on an integrative approach utilizing morphology, songs and mitochondrial and nuclear DNA for all taxa. All taxa were diagnosably different in plumage, and there were also structural differences among them, although the northernmost populations of owstoni (sometimes recognized as jakuschima and shonis ) were somewhat intermediate in plumage, structure and male plumage maturation between southern populations of owstoni and narcissina . All taxa had different songs, and a discriminant function analysis of four song variables correctly classified 100% of all songs. A strongly supported phylogeny was recovered based on three mitochondrial genes and three nuclear introns (total of 3543 bp), revealing a sister relationship between F. zanthopygia and the other taxa, between F. n. narcissina and F. n. owstoni, and between F. n. elisae and F. n. narcissina + F. n. owstoni . The corrected COI distances among the three F. narcissina subspecies ranged from 2.8% ( narcissina – owstoni ) to 8.2% ( narcissina – elisae ). We suggest that the congruent differences in multiple independent traits and the deep genetic divergences among the four taxa in the F. narcissina–F. zanthopygia complex support treatment of all of these taxa as separate species. However, we acknowledge the paucity of data for F. owstoni and recommend further studies of this taxon. We suggest listing both F. elisae and F. owstoni, which have small and fragmented populations, as globally threatened.